2017
DOI: 10.1103/physreve.95.062706
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-driven stability of defects in nematic textures over spherical disks

Abstract: Stabilizing defects in liquid-crystal systems is crucial for many physical processes and applications ranging from functionalizing liquid-crystal textures to recently reported command of chaotic behaviors of active matters. In this work, we perform analytical calculations to study the curvature driven stability mechanism of defects based on the isotropic nematic disk model that is free of any topological constraint. We show that in a growing spherical disk covering a sphere the accumulation of curvature effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The shape significantly differs from the proposed equilibrium shape in [27], where n-atic order on deformable surfaces is considered, but with a much simpler and purely intrinsic model. More recently, it has been demonstrated that besides these intrinsic curvature terms also extrinsic curvature terms, i. e. curvatures related to the geometry of the embedding space, are relevant [16,18,21,22,24,25,[41][42][43][44][45][46][47]. It has been demonstrated that the intrinsic geometry tends to confine topological defects to regions of maximal Gaussian curvature, while extrinsic couplings tend to orient the director field along minimal curvature lines.…”
Section: (D) Discussionmentioning
confidence: 99%
“…The shape significantly differs from the proposed equilibrium shape in [27], where n-atic order on deformable surfaces is considered, but with a much simpler and purely intrinsic model. More recently, it has been demonstrated that besides these intrinsic curvature terms also extrinsic curvature terms, i. e. curvatures related to the geometry of the embedding space, are relevant [16,18,21,22,24,25,[41][42][43][44][45][46][47]. It has been demonstrated that the intrinsic geometry tends to confine topological defects to regions of maximal Gaussian curvature, while extrinsic couplings tend to orient the director field along minimal curvature lines.…”
Section: (D) Discussionmentioning
confidence: 99%
“…Over the past two decades, important breakthroughs have been made in characterizing activestress driven matter flows in planar Euclidean geometries both theoretically [12][13][14][15][16][17][18][19][20][21][22][23] and experimentally [24][25][26][27][28][29][30]. More recently, theoretical work has begun to focus on incorporating curvature effects into active matter models [31][32][33][34][35][36][37][38][39][40]. Despite some promising progress, the hydrodynamic description of pattern-forming non-equilibrium liquids in non-Euclidean spaces continues to pose conceptual challenges, attributable to the difficulty of formulating exactly solvable continuum models and devising efficient spectral methods in curved geometries.…”
mentioning
confidence: 99%
“…Both shapes significantly differ from the proposed equilibrium shapes in 32 , where n−atic order on deformable surfaces is considered, but with a much simpler and purely intrinsic model. More recently, it has been demonstrated that besides these intrinsic curvature terms also extrinsic curvature terms, i. e. curvatures related to the geometry of the embedding space, are relevant 21,23,26,27,29,30,[45][46][47][48][49][50] . It has been demonstrated that the intrinsic geometry tends to confine topological defects to regions of maximal Gaussian curvature, while extrinsic couplings tend to orient the director field along minimal curvature lines.…”
Section: Discussionmentioning
confidence: 99%